Allyship Actually - Why it's 'We' and Not 'Me' - Barrow, David; Grimwade, Lucy (IT Governance Publishing, 2024)
Allyship Actually is a compelling and insightful exploration into the heart of true allyship-where performative gestures end and authentic solidarity begins. With honesty and clarity, this book (or article, talk, etc.) dismantles the myth that allyship is about personal virtue or visibility, emphasizing instead the collective, community-driven nature of real support. It unpacks how genuine allies listen, act, and uplift without centering themselves, shifting the focus from "look at me" to "stand with you."Whether you're just beginning your journey or seeking to deepen your understanding, Allyship Actually invites you to reimagine activism as a shared responsibility-rooted in humility, accountability, and action. This is not about leading the march alone, but walking together toward justice.